Kilpailukyky ja globaalin toimintaympäristön muutos: Suomen koneteollisuus maailmantaloudessa - Paavo Suni; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2011)
– The report analyses the impacts of globalization on competitiveness of national economies, industries and firms. The focus is in mechanical and electrical engineering and machinery. Global division of labor has significantly changed over the past few decades when the large emerging economies - notably China - have increased their role in world's industrial production. Prices of industrial goods relative to GDP prices of developed countries have been falling thereby pressing the price competitiveness of industrial-country-firms who have been looking for new competitive edge on the global market. This includes offshoring and outsourcing and moving to service provision. The Finnish mechanical and engineering industry has adapted to changing global competitive environment through major structural changes - the firm and plant structures have changed as consequence of exits and major reallocation of resources from less productive to higher productive units.
Keywords: F13; L60; L64; O12; 330; competitive edge; globalization; emerging economies; mechanical and electrical engineering; productivity; Globalisierung; Wettbewerb; Produktivität; Verarbeitendes Gewerbe; Finnland